AMPLITUDE AND SPEED INDICATORS OF MOTION MITRAL AND AORTIC HEART VALVES AND SPEED CIRCULAR SHORTENING FIBERS MYOCARDIUM OF THE LEFT VENTRICLE IN HEALTHY MEN AND WOMEN PODILLYA - Gunas, I.V.; Sheremeta, R.; Piliponova, V.; Rokunets, I. (World of Medicine and Biology, 2014)
In 109 practically healthy men aged from 22 to 35 years and 158 women aged from 21 to 35 years, residents of Podillya, by ultrasound of the heart set age and gender of echocardiographic amplitude and speed performance motion of the mitral and aortic valves of the heart rate and shortening of the circular fibers of myocardium of the left ventricle. Men and women of older age group most functional parameters were higher compared to individuals of similar gender age group. The amplitude of motion of the anterior mitral valve in a phase of rapid filling, opening of the aortic valve leaflets was significantly higher in the total group and men of different age groups than women of similar age. Speed circular fibers shortening of left ventricular in women aged from 26-35 years was significantly higher and in women aged from 21-25 years tends to larger values compared with men of similar age.
Keywords: echocardiography; first mature age; age differences; sexual dimorphism